2012
DOI: 10.1007/s00394-012-0407-4
|View full text |Cite
|
Sign up to set email alerts
|

Fate of dietary phytosteryl/-stanyl esters: analysis of individual intact esters in human feces

Abstract: The study revealed large interindividual variability regarding the recoveries of dietary phytosteryl/-stanyl esters upon gastrointestinal passage in healthy humans. Nevertheless, there was a significant impact of the acid moiety (oleate=linoleate=linolenate>eicosanoate>palmitate>ferulate) on the hydrolysis rates; the influence of the phytosterol/-stanol moiety was less pronounced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The PS profile in feces 3 and 4 resembles the composition of PS-enriched beverages. This has also been reported by Weststrate et al [14] in subjects consuming margarine enriched with PS esters (8.6 g PS/day), and by Lubinus et al [24] in feces from subjects ingesting three different fermented milks enriched with PS esters (2 g PS/day). Weststrate et al [14] reported that PS-enriched margarine intake significantly increased fecal neutral sterol excretion from about 40 mg/g to about 190 mg/g dry weight of feces, i.e., nearly fivefold.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The PS profile in feces 3 and 4 resembles the composition of PS-enriched beverages. This has also been reported by Weststrate et al [14] in subjects consuming margarine enriched with PS esters (8.6 g PS/day), and by Lubinus et al [24] in feces from subjects ingesting three different fermented milks enriched with PS esters (2 g PS/day). Weststrate et al [14] reported that PS-enriched margarine intake significantly increased fecal neutral sterol excretion from about 40 mg/g to about 190 mg/g dry weight of feces, i.e., nearly fivefold.…”
Section: Discussionsupporting
confidence: 78%
“…Feces from subjects that consume fat-rich foods (butter or corn oil) [10], PS-enriched foods such as margarine (6.8 g PS/day) [14] or skimmed milk yoghurt beverage (2 g/day) [24] have been analyzed in relation to neutral sterols and their metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies measured animal and plant sterols in blood and faecal samples (26,33) or plasma only (34) . Some studies examined faecal samples only in (short-to medium-term) intervention studies (1,25,26,33) .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The most widely used IS is 5α‐cholestane (Table ), though exceptionally other options such as nor‐cholic acid are also used. Cholesteryl acetate and cholesteryl cinnamate have been used in determining esterified forms . Besides, some authors use a surrogate standard (SS), this is a non‐target analyte that has chemical properties similar to those of the analyte of interest.…”
Section: Determination Of Dietary Sterols and Metabolites In Fecesmentioning
confidence: 99%
“…Cholesteryl acetate and cholesteryl cinnamate have been used in determining esterified forms. [98] Besides, some authors use a surrogate standard (SS), this is a non-target analyte that has chemical properties similar to those of the analyte of interest. A known concentration of SS is added at the start of the analysis, together with the sample, in order to evaluate the analyte response during the measurement.…”
Section: Internal Standard (Is)mentioning
confidence: 99%